A method for preparing a wear-resistant and corrosion-resistant coating for a wastewater treatment filter press

By using an inorganic salt matrix and stainless steel powder particles coated with MgO and porous TiO2-Al2O3 composite membranes, combined with the impregnation coating process, the problem of insufficient wear and corrosion resistance of the wastewater treatment filter press parts is solved, and higher wear and corrosion resistance and simpler preparation process is achieved.

CN117801580BActive Publication Date: 2025-04-15SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410003426.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-02
Publication Date
2025-04-15
Estimated Expiration
2044-01-02

AI Technical Summary

Technical Problem

The components of the wastewater treatment filter press are prone to wear and corrosion under harsh working conditions. The existing organic coatings are difficult to meet the requirements of their wear and corrosion resistance, and the preparation process is complicated.

Method used

Based on the inorganic salt matrix and stainless steel powder particles, MgO curing agent was prepared by sol-gel method and coated on the surface of stainless steel powder particles to form a porous TiO2-Al2O3 composite film, and a wear-resistant and corrosion-resistant coating was prepared in combination with the dip coating process.

Benefits of technology

It realizes that the wear resistance and corrosion resistance of wastewater treatment filter press parts is significantly improved without changing the structure, extends the service life, and simplifies the coating preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention discloses a method for preparing a wear-resistant and corrosion-resistant coating for a wastewater treatment filter press, which is characterized in that an AlPO4 inorganic salt matrix of the wear-resistant and corrosion-resistant coating is first prepared, and then a micron-grade stainless steel powder is used as the second phase of the wear-resistant and corrosion-resistant coating to prepare a stable dispersion system, and the surface of the second phase is modified to obtain stainless steel powder particles whose surfaces are sequentially coated with MgO and a porous TiO2-Al2O3 composite film, and the surface-modified stainless steel powder particles are mixed with the inorganic salt matrix and dip-coated on the surface of the wastewater treatment filter press parts to achieve the preparation of the wear-resistant and corrosion-resistant coating. The invention overcomes the problems of insufficient performance and complicated preparation process of the existing wear-resistant and corrosion-resistant coating, and can be used to prepare the protective coating of the wastewater treatment filter press.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a wear-resistant and corrosion-resistant coating, in particular to a method for preparing a wear-resistant and corrosion-resistant coating for a wastewater treatment filter press, and belongs to the field of surface engineering. Background Art

[0002] Filter presses are widely used in the sludge dewatering process in the (phosphorus, fluorine) chemical industry, steel metallurgy, food and pharmaceutical industry, and environmental engineering wastewater treatment. Their core components often fail due to wear and corrosion. Coating filter press components is the main technical direction to meet the increasingly high use requirements and achieve long-life operation of filter presses.

[0003] CN202210031855.5 discloses a filter plate for a filter press, wherein the filter plate body comprises a filter frame and two filter membranes, a feed hole is provided at the center of the filter plate body, an anti-adhesion component is arranged on the filter plate body, the filter frame comprises a substrate layer, anti-corrosion coatings are fixedly connected to the outer walls on both sides of the substrate layer, and wear-resistant coatings are fixedly connected to the sides of the two anti-corrosion coatings away from each other, wherein the anti-corrosion coating is a polyurethane anti-corrosion coating, and the wear-resistant coating is a ceramic wear-resistant coating. CN202110977849.4 discloses a polyurea anti-corrosion liquid receiving flap of an anti-corrosion filter press and a method for spraying polyurea for anti-corrosion. The liquid receiving flap includes an active flap and a passive flap - including a stainless steel liquid receiving plate, a carbon steel flap shaft, a wear-resistant bearing box, a flap frame, a stainless steel liquid collecting tank, a dual-drive fork, and a polyurea anti-corrosion layer; after sandblasting and rust removal and surface treatment (spraying interface agent) on the surfaces of the metal active flap and passive flap that contact the corrosive liquid, a polyurea sprayer is used to spray a layer of a new polyurea anti-corrosion layer with a thickness of about 1.5 mm to form a polyurea anti-corrosion liquid receiving flap that is resistant to corrosion, wear and aging.

[0004] CN201811617205.9 discloses a wear-resistant oil seal bushing for a filter press, comprising a guide roller shaft and an oil seal bushing, wherein one end of the guide roller shaft is slidably sleeved with the oil seal bushing, an upper end of the oil seal bushing is fixedly provided with an oblique mouth, an inner side of the oil seal bushing is fixedly provided with a through hole, and the inner wall surface of the oil seal bushing is fixedly provided with sprayed ceramics. Compared with the prior art, the present invention has the following beneficial effects: the product has a simple and practical structure, and the service life of the oil seal bushing is improved without changing the structure. Ceramic is sprayed on the inner wall of the oil seal bushing and then polished to form a 0.25MM ceramic spray layer. At the same time, the surface finish can reach above 0.4, thereby extending the service life and maintenance time of the guide roller bearing.

[0005] CN200910227880.5 discloses a method for repairing a plastic filter plate of a filter press, comprising: 1) replacing the worn part of a polypropylene filter plate with a modified ultra-high molecular weight polyethylene small filter plate; 2) coating a layer of epoxy resin wear-resistant material on the surface and periphery of the filter plate where the small filter plate has been replaced; 3) pre-laying a resistance filter cloth on the surface of the filter plate coated with the epoxy resin wear-resistant material. The present invention repairs the plastic filter plate of the filter press that has been scrapped due to damage in a series structure by adopting three wear-resistant strengthening measures, namely, replacing the material in the worn area, coating the surface with epoxy resin wear-resistant coating, and laying the resistance filter cloth, thus playing the role of three "defense lines", increasing the anti-wear effect of the filter plate on fine solid particles in the filtrate, and increasing the normal service life of the filter plate from less than 3 months to more than 10 months, and increasing the wear resistance by more than 3 times.

[0006] However, the service conditions of wastewater treatment filter presses are becoming increasingly harsh, and the requirements for wear and corrosion resistance are becoming increasingly higher. It is necessary to coat the key components of wastewater treatment filter presses to meet the working conditions and increase their service life. Most of the existing coatings are organic coatings, which are difficult to meet the comprehensive requirements of wear and corrosion resistance of coatings under harsh working conditions. The preparation process is complicated, and it is urgent to develop inorganic wear and corrosion resistant coatings. Summary of the invention

[0007] In view of the problems existing in the preparation of wear-resistant and corrosion-resistant coatings for wastewater treatment filter presses, the present invention first prepares an inorganic salt matrix of the wear-resistant and corrosion-resistant coating, then prepares a second phase dispersion system of the wear-resistant and corrosion-resistant coating, and modifies the surface of the second phase to obtain stainless steel powder particles whose surfaces are sequentially coated with MgO and a porous TiO2-Al2O3 composite film, mixes the surface-modified stainless steel powder particles with the inorganic salt matrix, and dips the coating on the surface of the wastewater treatment filter press parts to achieve the preparation of the wear-resistant and corrosion-resistant coating.

[0008] The method for preparing the wear-resistant and corrosion-resistant coating for the wastewater treatment filter press of the present invention is characterized in that it comprises the following steps in sequence:

[0009] (1) Preparation of inorganic salt matrix of wear-resistant and corrosion-resistant coating: A solution was prepared with H3PO4 and Al(OH)3 as raw materials, and the molar concentration of Al(OH)3 was 45-50%. The solution was magnetically stirred in a constant temperature water bath at 95°C for 1-2 hours. H3PO4 and Al(OH)3 reacted to generate an inorganic salt matrix of wear-resistant and corrosion-resistant coating with AlPO4 as the phase;

[0010] (2) Preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating: Stainless steel powder with a particle size of d50 = 8-12 μm is added to anhydrous ethanol, with the stainless steel powder accounting for 10-15% by weight and the rest being anhydrous ethanol; the mixture of stainless steel and anhydrous ethanol is then subjected to planetary ball milling for 12-24 h and filtered through a 200-mesh stainless steel sieve to form a stainless steel slurry; oleic acid accounting for 2-3 vol% of the slurry is added to the stainless steel slurry, and ammonia water is added to adjust the pH value of the slurry to 8-9, so that the Zeta potential of the slurry is 20-30 mV, thereby forming a stable second phase dispersion system of the wear-resistant and corrosion-resistant coating;

[0011] (3) Second phase surface modification of wear-resistant and corrosion-resistant coating: First, MgSO4 and deionized water were mixed to form a solution with a molar concentration of 1% to 3%, and ammonia water was added to adjust the pH value of the solution to 8 to 9. After magnetic stirring for 1 to 3 hours in a constant temperature water bath at 70 to 80°C, Mg(OH)2 sol was formed. Then, the Mg(OH)2 sol was mixed with the second phase dispersion system of the wear-resistant and corrosion-resistant coating in a volume ratio of 1: (1 to 3), and magnetic stirring was carried out for 1 to 3 hours in a constant temperature water bath at 70 to 80°C to coat the surface of the stainless steel powder particles with Mg(OH)2. After standing for 24 hours to form a gel, it was washed with deionized water for 4 to 6 times and filtered, dried at 100 to 120°C, and heated at 400 to 600°C. ℃ calcined for 1~2h to obtain stainless steel powder particles with MgO coated on the surface; polyoxyethylene, anhydrous ethanol and deionized water were mixed to prepare a composite solvent, the weight ratio of the three was (0.1~0.5):100:100, and then butyl titanate and Al(NO3)3 were added to prepare a solution, the molar percentage concentration of butyl titanate in the solution was 1%~3%, and the molar percentage concentration of Al(NO3)3 was 1%~3%; magnetic stirring was carried out at room temperature for 1~3h to form a Ti(OH)4-Al(OH)3 composite sol; the stainless steel powder particles with MgO coated on the surface were mixed with propylene oxide according to the weight percentage of 1:(0.3~0.6):(2~4) The mixture was added into Ti(OH)4-Al(OH)3 composite sol, stirred magnetically for 3-5 min in a constant temperature water bath at 40-45°C, and then placed at the same temperature for 24 h for gelation. During the gelation process, polyethylene oxide was adsorbed on TiO2-Al2O3 oligomers through hydrogen bonds to form a PEO-rich phase, and repelled from the aqueous phase to form a water-rich phase, that is, a phase-separated gel consisting of a PEO-rich phase and a water-rich phase was formed. The gel was then washed 4-6 times with anhydrous ethanol and filtered, and heated to 100-120°C at a heating rate of 1-3°C / min and kept warm for 1-2 h for drying, and then heated to 500-600°C at a heating rate of 1-3°C / min and calcined for 1-2 h to remove organic matter, and a porous TiO2-Al2O3 composite membrane was formed on the surface of the stainless steel powder particles coated with MgO, with a pore size of 0.5-2 μm and a pore volume of 0.3-0.7 cm 3 / g; obtaining stainless steel powder particles whose surfaces are sequentially coated with MgO and porous TiO2-Al2O3 composite films, completing the second phase surface modification preparation of the wear-resistant and corrosion-resistant coating;

[0012] (4) Preparation of wear-resistant and corrosion-resistant coating: The second phase of the wear-resistant and corrosion-resistant coating that has been prepared after surface modification, i.e., the stainless steel powder particles whose surface is coated with MgO and porous TiO2-Al2O3 composite film in sequence, is mixed with the inorganic salt matrix of the wear-resistant and corrosion-resistant coating in a weight percentage (0.5~1):10, and stirred at room temperature for 30~60 minutes to prepare the coating; the coating should be applied within 24 hours, first the parts to be coated are sandblasted, and then the coating is applied to the surface of the wastewater treatment filter press parts by dip coating, and then placed in the air at room temperature for more than 24 hours until the weight loss rate of the parts is less than 0.1g / (m 2 h) the curing of the wear-resistant and corrosion-resistant coating is completed.

[0013] The method for preparing the wear-resistant and corrosion-resistant coating for the wastewater treatment filter press of the present invention is further characterized in that:

[0014] (1) The H3PO4 and Al(OH)3 used in the preparation of the inorganic salt matrix of the wear-resistant and corrosion-resistant coating are both analytically pure;

[0015] (2) The ammonia water, oleic acid and anhydrous ethanol used in the preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating were all analytically pure; stainless steel balls with a diameter of 10 mm were used in ball milling, the ball-to-material weight ratio was 5:1, and the ball mill speed was 200~300r / min;

[0016] (3) The MgSO4, butyl titanate, Al(NO3)3, polyethylene oxide, ammonia water, anhydrous ethanol and propylene oxide used in the second phase surface modification treatment of the wear-resistant and corrosion-resistant coating were all analytically pure;

[0017] (4) When preparing the wear-resistant and corrosion-resistant coating, the stirring rate of the coating is 100~150 r / min; before coating, the parts to be coated are sandblasted with alumina particles with a particle size of 80~120 mesh at a pressure of 0.5~0.7 MPa for 2~5 minutes. The nozzle is 50~100 mm away from the parts to be coated, and the angle between the spray direction and the surface normal of the parts to be coated is controlled at 15~30°; when dipping the coating, the dipping time is 10~15 minutes.

[0018] The advantages of the present invention are as follows: (1) In the present invention, an inorganic salt with a physical phase of AlPO4 is prepared as a coating matrix, and micron-sized stainless steel powder particles are used as the second phase, so that the coating has both wear resistance and corrosion resistance. (2) A sol-gel method is used to prepare a MgO curing agent, and MgO is coated on the surface of the second phase of the stainless steel powder particles, so that the curing agent is uniformly dispersed in the AlPO4 inorganic salt matrix, which is conducive to the uniform curing process of the coating. (3) A porous TiO2-Al2O3 composite film is formed on the surface of the stainless steel powder particles coated with MgO by a sol-gel method, so that the MgO curing agent is prevented from directly contacting the AlPO4 inorganic salt matrix, so that slow release and slow curing are achieved, the requirements for coating in the project are met, and cracks caused by rapid curing of the coating are avoided. (4) The porous TiO2-Al2O3 composite film can not only control the release of the curing agent, but also improve the physical and chemical compatibility between the stainless steel second phase and the AlPO4 inorganic salt matrix, reduce coating defects, and improve the wear resistance and corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the method for preparing the wear-resistant and corrosion-resistant coating for the wastewater treatment filter press of the present invention. DETAILED DESCRIPTION

[0020] Example 1: Prepare the wear-resistant and corrosion-resistant coating for wastewater treatment filter press according to the following steps:

[0021] (1) Preparation of inorganic salt matrix of wear-resistant and corrosion-resistant coating: A solution was prepared with analytically pure H3PO4 and Al(OH)3 as raw materials, and the molar concentration of Al(OH)3 was 45%. The solution was magnetically stirred in a constant temperature water bath at 95°C for 1 hour. H3PO4 and Al(OH)3 reacted to generate an inorganic salt matrix of wear-resistant and corrosion-resistant coating with AlPO4 as the phase;

[0022] (2) Preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating: Stainless steel powder with a particle size of d50 = 9 μm was added to anhydrous ethanol, with the stainless steel powder accounting for 10% by weight and the rest being anhydrous ethanol; the mixture of stainless steel and anhydrous ethanol was then subjected to planetary ball milling for 12 h, using stainless steel balls with a diameter of 10 mm, a ball-to-material weight ratio of 5:1, and a ball mill speed of 200 r / min; a stainless steel slurry was formed after filtering with a 200-mesh stainless steel sieve; oleic acid accounting for 2 vol% of the slurry was added to the stainless steel slurry, and ammonia water was added to adjust the pH value of the slurry to 8, so that the Zeta potential of the slurry was 22 mV, thereby forming a stable second phase dispersion system of the wear-resistant and corrosion-resistant coating; the ammonia water, oleic acid, and anhydrous ethanol used in the preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating were all analytically pure;

[0023] (3) Second phase surface modification of wear-resistant and corrosion-resistant coating: MgSO4 and deionized water were first mixed to form a solution with a molar concentration of 1%, and ammonia water was added to adjust the pH value of the solution to 8. After magnetic stirring in a constant temperature water bath at 70°C for 1 hour, Mg(OH)2 sol was formed. Then, the Mg(OH)2 sol was mixed with the second phase dispersion system of the wear-resistant and corrosion-resistant coating in a volume ratio of 1:1, and magnetic stirring was carried out in a constant temperature water bath at 70°C for 1 hour to coat the surface of the stainless steel powder particles with Mg(OH)2. After standing for 24 hours to form a gel, the mixture was washed 4 times with deionized water and filtered, dried at 100°C, and calcined at 400°C for 1 hour to obtain stainless steel powder particles with MgO coated on the surface. Polyoxyethylene, anhydrous ethanol and deionized water were mixed to form a composite solvent with a weight ratio of 0.1:100:100, and then butyl titanate and Al(NO3)3 were added to form a solution with orthobutyl titanate in the solution. The molar concentration of butyl titanate is 1%, and the molar concentration of Al(NO3)3 is 2%. The mixture is magnetically stirred at room temperature for 1 hour to form a Ti(OH)4-Al(OH)3 composite sol. Stainless steel powder particles coated with MgO and propylene oxide are added to the Ti(OH)4-Al(OH)3 composite sol in a weight percentage of 1:0.3:2. The mixture is magnetically stirred in a constant temperature water bath at 40°C for 3 minutes and then placed at the same temperature for 24 hours for gelation. During the gelation process, polyethylene oxide is adsorbed on the TiO2-Al2O3 oligomer through hydrogen bonds to form a PEO-rich phase, and mutually repel the aqueous phase to form a water-rich phase, that is, a phase-separated gel consisting of a PEO-rich phase and a water-rich phase is formed. The gel is then washed 4 times with anhydrous ethanol and filtered, and heated to 100°C at a heating rate of 1°C / min and kept warm for 1 hour for drying, and then heated to 500°C at a heating rate of 1°C / min. ℃ calcined for 1h to remove organic matter and form a porous TiO2-Al2O3 composite film on the surface of the stainless steel powder particles coated with MgO, with a pore size of 0.5~2μm and a pore volume of 0.32cm 3 / g; stainless steel powder particles whose surfaces are sequentially coated with MgO and porous TiO2-Al2O3 composite films are obtained, and the second phase surface modification preparation of the wear-resistant and corrosion-resistant coating is completed; the MgSO4, butyl orthotitanate, Al(NO3)3, polyethylene oxide, ammonia water, anhydrous ethanol, and propylene oxide used in the second phase surface modification treatment of the wear-resistant and corrosion-resistant coating are all analytically pure;

[0024] (4) Preparation of wear-resistant and corrosion-resistant coating: The second phase of the wear-resistant and corrosion-resistant coating that has been prepared after surface modification, i.e., the stainless steel powder particles whose surface is coated with MgO and porous TiO2-Al2O3 composite film in sequence, is mixed with the inorganic salt matrix of the wear-resistant and corrosion-resistant coating in a weight percentage of 0.5:10, and stirred at room temperature for 30 minutes to prepare the coating, with a stirring rate of 100 r / min; the coating should be applied within 24 hours, and before coating, the parts to be coated are sandblasted for 2 minutes using alumina particles with a particle size of 80 mesh at a pressure of 0.5 MPa, with the nozzle 60 mm away from the parts to be coated, and the angle between the spray direction and the surface normal of the parts to be coated is controlled at 15°; the coating is then applied to the surface of the wastewater treatment filter press parts by dip coating, and the dipping time is 10 minutes; after dip coating, the coating is placed in air at room temperature for more than 24 hours until the weight loss rate of the parts is less than 0.1 g / (m 2 h) the curing of the wear-resistant and corrosion-resistant coating is completed.

[0025] Example 2: Prepare the wear-resistant and corrosion-resistant coating for the wastewater treatment filter press according to the following steps:

[0026] (1) Preparation of inorganic salt matrix of wear-resistant and corrosion-resistant coating: A solution was prepared with analytically pure H3PO4 and Al(OH)3 as raw materials, and the molar concentration of Al(OH)3 was 50%. The solution was magnetically stirred in a constant temperature water bath at 95°C for 2 hours. H3PO4 and Al(OH)3 reacted to generate an inorganic salt matrix of wear-resistant and corrosion-resistant coating with AlPO4 as the phase;

[0027] (2) Preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating: Stainless steel powder with a particle size of d50 = 10 μm was added to anhydrous ethanol, with the stainless steel powder accounting for 15% by weight and the rest being anhydrous ethanol; the mixture of stainless steel and anhydrous ethanol was then subjected to planetary ball milling for 20 h, using stainless steel balls with a diameter of 10 mm, a ball-to-material weight ratio of 5:1, and a ball mill speed of 250 r / min; a stainless steel slurry was formed after filtering with a 200-mesh stainless steel screen; oleic acid accounting for 3 vol% of the slurry was added to the stainless steel slurry, and ammonia water was added to adjust the pH value of the slurry to 9, so that the Zeta potential of the slurry was 28 mV, thereby forming a stable second phase dispersion system of the wear-resistant and corrosion-resistant coating; the ammonia water, oleic acid, and anhydrous ethanol used in the preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating were all analytically pure;

[0028] (3) Surface modification of the second phase of the wear-resistant and corrosion-resistant coating: MgSO4 and deionized water were first mixed to form a solution with a molar concentration of 3%, and ammonia water was added to adjust the pH value of the solution to 9. After magnetic stirring for 3 hours in a constant temperature water bath at 75°C, Mg(OH)2 sol was formed. Then, the Mg(OH)2 sol was mixed with the second phase dispersion system of the wear-resistant and corrosion-resistant coating in a volume ratio of 1:2, and magnetic stirring was carried out for 2 hours in a constant temperature water bath at 80°C to coat the surface of the stainless steel powder particles with Mg(OH)2. After standing for 24 hours to form a gel, it was washed with deionized water for 6 times and filtered, dried at 120°C, and dried at 600°C. ℃ calcined for 1h to obtain stainless steel powder particles with MgO coated on the surface; polyoxyethylene, anhydrous ethanol and deionized water were mixed to prepare a composite solvent, the weight ratio of the three was 0.5:100:100, and then butyl titanate and Al(NO3)3 were added to prepare a solution, the molar percentage concentration of butyl titanate in the solution was 2%, and the molar percentage concentration of Al(NO3)3 was 3%; magnetic stirring was carried out at room temperature for 2h to form a Ti(OH)4-Al(OH)3 composite sol; stainless steel powder particles with MgO coated on the surface and propylene oxide were added according to the weight percentage of 1:0.5:3 The mixture was added to Ti(OH)4-Al(OH)3 composite sol, stirred magnetically for 5 min in a constant temperature water bath at 45°C, and then placed at the same temperature for 24 h for gelation. During the gelation process, polyethylene oxide was adsorbed on the TiO2-Al2O3 oligomers through hydrogen bonds to form a PEO-rich phase, and repelled from the aqueous phase to form a water-rich phase, that is, a phase-separated gel consisting of a PEO-rich phase and a water-rich phase was formed. The gel was then washed 6 times with anhydrous ethanol and filtered, and heated to 120°C at a heating rate of 3°C / min and kept warm for 2 h for drying. It was then heated to 600°C at a heating rate of 3°C / min and calcined for 2 h to remove organic matter, and a porous TiO2-Al2O3 composite membrane was formed on the surface of the stainless steel powder particles coated with MgO, with a pore size of 0.5-2 μm and a pore volume of 0.63 cm 3 / g; stainless steel powder particles whose surfaces are sequentially coated with MgO and porous TiO2-Al2O3 composite films are obtained, and the second phase surface modification preparation of the wear-resistant and corrosion-resistant coating is completed; the MgSO4, butyl orthotitanate, Al(NO3)3, polyethylene oxide, ammonia water, anhydrous ethanol, and propylene oxide used in the second phase surface modification treatment of the wear-resistant and corrosion-resistant coating are all analytically pure;

[0029] (4) Preparation of wear-resistant and corrosion-resistant coating: The second phase of the wear-resistant and corrosion-resistant coating that has been prepared after surface modification, i.e., the stainless steel powder particles whose surface is coated with MgO and porous TiO2-Al2O3 composite film in sequence, is mixed with the inorganic salt matrix of the wear-resistant and corrosion-resistant coating in a weight percentage of 0.8:10, and stirred at room temperature for 50 minutes to prepare the coating, with a stirring rate of 150 r / min; the coating should be applied within 24 hours, and before coating, the parts to be coated are sandblasted for 5 minutes with alumina particles with a particle size of 100 mesh at a pressure of 0.7 MPa, with the nozzle 100 mm away from the parts to be coated, and the angle between the spray direction and the surface normal of the parts to be coated is controlled at 20°; the coating is then applied to the surface of the wastewater treatment filter press parts by dip coating, and the dipping time is 15 minutes; after dip coating, the coating is placed in air at room temperature for more than 24 hours until the weight loss rate of the parts is less than 0.1g / (m 2 h) the curing of the wear-resistant and corrosion-resistant coating is completed.

Claims

1. A method for preparing a wear-resistant and corrosion-resistant coating for a wastewater treatment filter press, characterized in that The following steps are included in sequence: (1) Preparation of inorganic salt matrix of wear-resistant and corrosion-resistant coating: A solution was prepared with H3PO4 and Al(OH)3 as raw materials, and the molar concentration of Al(OH)3 was 45-50%. The solution was magnetically stirred in a constant temperature water bath at 95°C for 1-2 hours. H3PO4 and Al(OH)3 reacted to generate an inorganic salt matrix of wear-resistant and corrosion-resistant coating with AlPO4 as the phase; (2) Preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating: Stainless steel powder with a particle size of d50 = 8-12 μm is added to anhydrous ethanol, with the stainless steel powder accounting for 10-15% by weight and the rest being anhydrous ethanol; the mixture of stainless steel and anhydrous ethanol is then subjected to planetary ball milling for 12-24 h and filtered through a 200-mesh stainless steel sieve to form a stainless steel slurry; oleic acid accounting for 2-3 vol% of the slurry is added to the stainless steel slurry, and ammonia water is added to adjust the pH value of the slurry to 8-9, so that the Zeta potential of the slurry is 20-30 mV, thereby forming a stable second phase dispersion system of the wear-resistant and corrosion-resistant coating; (3) Surface modification of the second phase of the wear-resistant and corrosion-resistant coating: MgSO4 was first mixed with deionized water to form a solution with a molar concentration of 1% to 3%, and ammonia water was added to adjust the pH value of the solution to 8 to 9. After magnetic stirring in a constant temperature water bath at 70 to 80°C for 1 to 3 hours, Mg(OH)2 sol was formed. Then, the Mg(OH)2 sol was mixed with the second phase dispersion system of the wear-resistant and corrosion-resistant coating in a volume ratio of 1: (1 to 3), and magnetic stirring was carried out in a constant temperature water bath at 70 to 80°C for 1 to 3 hours to coat the surface of the stainless steel powder particles with Mg(OH)2. After standing for 24 hours to form a gel, it was washed with deionized water for 4 to 6 times and filtered, dried at 100 to 120°C, and heated at 400 to 600°C. ℃ calcined for 1~2h to obtain stainless steel powder particles with MgO coated on the surface; polyoxyethylene, anhydrous ethanol and deionized water were mixed to prepare a composite solvent, the weight ratio of the three was (0.1~0.5):100:100, and then butyl titanate and Al(NO3)3 were added to prepare a solution, the molar percentage concentration of butyl titanate in the solution was 1%~3%, and the molar percentage concentration of Al(NO3)3 was 1%~3%; magnetic stirring was carried out at room temperature for 1~3h to form a Ti(OH)4-Al(OH)3 composite sol; the stainless steel powder particles with MgO coated on the surface were mixed with propylene oxide according to the weight percentage of 1:(0.3~0.6):(2~4) The mixture was added into Ti(OH)4-Al(OH)3 composite sol, stirred magnetically for 3-5 min in a constant temperature water bath at 40-45°C, and then placed at the same temperature for 24 h for gelation. During the gelation process, polyethylene oxide was adsorbed on TiO2-Al2O3 oligomers through hydrogen bonds to form a PEO-rich phase, and repelled from the aqueous phase to form a water-rich phase, that is, a phase-separated gel consisting of a PEO-rich phase and a water-rich phase was formed. The gel was then washed 4-6 times with anhydrous ethanol and filtered, and heated to 100-120°C at a heating rate of 1-3°C / min and kept warm for 1-2 h for drying, and then heated to 500-600°C at a heating rate of 1-3°C / min and calcined for 1-2 h to remove organic matter, and a porous TiO2-Al2O3 composite membrane was formed on the surface of the stainless steel powder particles coated with MgO, with a pore size of 0.5-2 μm and a pore volume of 0.3-0.7 cm 3 / g; obtaining stainless steel powder particles whose surfaces are sequentially coated with MgO and porous TiO2-Al2O3 composite films, completing the second phase surface modification preparation of the wear-resistant and corrosion-resistant coating; (4) Preparation of wear-resistant and corrosion-resistant coating: The prepared second phase of the wear-resistant and corrosion-resistant coating after surface modification, i.e., the stainless steel powder particles whose surface is coated with MgO and porous TiO2-Al2O3 composite film in sequence, is mixed with the inorganic salt matrix of the wear-resistant and corrosion-resistant coating in a weight percentage (0.5~1):10, and stirred at room temperature for 30~60 minutes to prepare the coating; the coating should be applied within 24 hours, first the parts to be coated are sandblasted, and then the coating is applied to the surface of the wastewater treatment filter press parts by dip coating, and then placed in the air at room temperature for more than 24 hours until the weight loss rate of the parts is less than 0.1g / (m 2 h) the curing of the wear-resistant and corrosion-resistant coating is completed.

2. The method for preparing the wear-resistant and corrosion-resistant coating for the wastewater treatment filter press according to claim 1 is further characterized in that: (1) The H3PO4 and Al(OH)3 used in the preparation of the inorganic salt matrix of the wear-resistant and corrosion-resistant coating are both analytically pure; (2) The ammonia water, oleic acid and anhydrous ethanol used in the preparation of the second phase dispersion system of the wear-resistant and corrosion-resistant coating were all analytically pure; stainless steel balls with a diameter of 10 mm were used in ball milling, the ball-to-material weight ratio was 5:1, and the ball mill speed was 200~300r / min; (3) The MgSO4, butyl titanate, Al(NO3)3, polyethylene oxide, ammonia water, anhydrous ethanol and propylene oxide used in the second phase surface modification treatment of the wear-resistant and corrosion-resistant coating were all analytically pure; (4) When preparing the wear-resistant and corrosion-resistant coating, the stirring rate of the coating is 100~150 r / min; before coating, the parts to be coated are sandblasted with alumina particles with a particle size of 80~120 mesh at a pressure of 0.5~0.7 MPa for 2~5 minutes. The nozzle is 50~100 mm away from the parts to be coated, and the angle between the spray direction and the surface normal of the parts to be coated is controlled at 15~30°; when dipping the coating, the dipping time is 10~15 minutes.

Citation Information

Patent Citations

  • Method for repairing plastic filter plate of filter press

    CN101708660A

  • Wear-resisting filter press oil seal bush

    CN109441950A

  • Polyurea anti-corrosion type liquid receiving turning plate of anti-corrosion filter press and polyurea spraying anti-corrosion method thereof

    CN113559574A

  • Filter plate for filter press

    CN114344960A

  • Anticorrosive coating for metal surfaces

    CN109233562A